Lidocaine, old drug - new possibilities. Treatment of postoperative pain and reduction of postoperative complications with intravenous administration - Kamil Budzeń; Paweł Wesołowski; Sebastian Bąk; Tomasz Stachura; Przemysław Żelazny (Kazimierz Wielki University, 2022)
Introduction: The number of surgeries requiring sedation continues to increase worldwide. Analgesia is one of the main components of anesthesia used during surgical procedures. Despite improvements in surgical techniques, the invention of new analgesics and a significant expansion of knowledge about the pathophysiology of pain, more than 75% of patients experience postoperative pain. Adequate analgesia reduces postoperative complications and shortens the length of hospitalization. Lidocaine is a local anesthetic also used as an antiarrhythmic drug. Studies report that intravenous administration may find application in perioperative analgesia. Aim of the study: The purpose of our study was to determine in which types of surgery the benefits of IVL (Intravenous lidocaine) are greatest. Methods and Evidence: We reviewed the literature available on PubMed using the words "Intravenous lidocaine"; "Perioperative Lidocaine "; "Postoperative pain". Results: IVL has been shown to have a positive effect on reducing opioid doses, postoperative pain intensity, shortening the duration of postoperative bowel obstruction, faster patient rehabilitation and shortening hospitalization. In non-abdominal surgeries, the greatest benefits have been seen in breast surgery, urology and spinal surgery. Lidocaine has low toxicity; only doses several times higher cause adverse effects. Conclusions: IVL should be used during intraabdominal surgery due to its high efficacy. Further studies on a larger group of patients are needed to better determine the effects of IVL in other surgeries. Keywords: "Intravenous lidocaine"; "Perioperative Lidocaine "; "Postoperative pain".